Planning or propaganda? An evaluation of Germany's medium-term budgetary planning - Friedrich Heinemann (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
In Germany, the medium-term financial planning ("Mifrifi") was introduced at the end of the sixties. This study scrutinizes the experience of the German Bund with more than thirty years of financial planning. In the first step, the paper explores the potential normative and political-economic driving forces of fiscal projections. The following empirical part evaluates Mifrifi?s forecasting quality with regard to expenditures, taxes and deficits. A model is tested relating the forecasted budgetary trends to economic, institutional and political-economic factors. The financial planning turns out to be ineffective in making budgetary policy more predictable. The projections are heavily biased towards over-optimism. The Maastricht Treaty appears to have transformed Germany?s budgetary planning not into the direction of more credible and binding projections, but rather towards the production of less realistic and unduly favourable outlooks. The policy conclusion hints towards an independent institution taking over the responsibility for fiscal forecasts. Such an institution would not face the government?s inherent problem being unable to promise in a credible way the production of unbiased forecasts.
Keywords: H87; H61; 330; Mifrifi; budgetary planning; Stability and Growth Pact; Öffentliche Finanzplanung; EU-Stabilitätspakt; Wirtschaftspolitische Wirkungsanalyse; Deutschland